PENGARUH CORPORATE SOSIAL RESPONSIBILITY (CSR) DAN LEVERAGE TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Firmansyah Firmansyah; Martiana Dwi Anggraeni (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2022)
The purpose of this study was to determine the effect of Corporate Social Responsibility (CSR) and Leverage on kinerja perusahaan both partially and simultaneously. In this study, Corporate Social Responsibility (CSR) is measured by GRI Standards which focus on disclosure of social standards, leverage is measured by Debt to Equity Ratio (DER), while kinerja perusahaan is measured by Return On Asset (ROA). The sample used in this study is a manufacturing company in the consumer goods industry which is listed on the Indonesia Stock Exchange in 2015-2019. By using purposive sampling method, there are 13 companies that meet the criteria to be sampled in this study. Data is collected by downloading annual report data through the website www.idx.co.id. The analytical method used is multiple linear regression analysis, descriptive statistical analysis in this study using the IBM SPSS version 22.0 program. The results of this study indicate that partially Corporate Social Responsibility (CSR) has no effect on Return On Assets (ROA), because the t test results on the CSR variable show that the t-count value is smaller than the t-table (-1.719 2,000), while the Debt to Equity Ratio (DER) has a effect on Return On Assets (ROA), because the results of the t test on the DER variable show that the t-count is smaller than the t-table (-6,307 2,00). Simultaneously (together) Corporate Social Responsibility (CSR) and Debt to Equity Ratio (DER) have a significant effect on Return on Assets (ROA) because the F test results show that the value of Fcount Ftable (19,915 3,14).